KCa3.1 Mediates Dysregulation of Mitochondrial Quality Control in Diabetic Kidney Disease - Huang, Chunling; Yi, Hao; Shi, Ying; Cao, Qinghua; Shi, Yin; Cheng, Delfine; Braet, Filip; Chen, Xin-Ming; Pollock, Carol A. (Frontiers in Cell and Developmental Biology, 2021)
Mitochondrial dysfunction is implicated in the pathogenesis of diabetic kidney disease. Mitochondrial quality control is primarily mediated by mitochondrial turnover and repair through mitochondrial fission/fusion and mitophagy. We have previously shown that blockade of the calcium-activated potassium channel KCa3.1 ameliorates diabetic renal fibrosis. However, the mechanistic link between KCa3.1 and mitochondrial quality control in diabetic kidney disease is not yet known. Transforming growth factor β1 (TGF-β1) plays a central role in diabetic kidney disease. Recent studies indicate an emerging role of TGF-β1 in the regulation of mitochondrial function. However, the molecular mechanism mediating mitochondrial quality control in response to TGF-β1 remains limited. In this study, mitochondrial function was assessed in TGF-β1-exposed renal proximal tubular epithelial cells (HK2 cells) transfected with scrambled siRNA or KCa3.1 siRNA. In vivo, diabetes was induced in KCa3.1+/+ and KCa3.1−/− mice by low-dose streptozotocin (STZ) injection. Mitochondrial fission/fusion-related proteins and mitophagy markers, as well as BCL2 interacting protein 3 (BNIP3) (a mitophagy regulator) were examined in HK2 cells and diabetic mice kidneys. The in vitro results showed that TGF-β1 significantly inhibited mitochondrial ATP production rate and increased mitochondrial ROS (mtROS) production when compared to control, which was normalized by KCa3.1 gene silencing. Increased fission and suppressed fusion were found in both TGF-β1-treated HK2 cells and diabetic mice, which were reversed by KCa3.1 deficiency. Furthermore, our results showed that mitophagy was inhibited in both in vitro and in vivo models of diabetic kidney disease. KCa3.1 deficiency restored abnormal mitophagy by inhibiting BNIP3 expression in TGF-β1-induced HK2 cells as well as in the diabetic mice. Collectively, these results indicate that KCa3.1 mediates the dysregulation of mitochondrial quality control in diabetic kidney disease.